The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41539-019-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender similarities in the brain during mathematics development

Abstract: Some scientists and public figures have hypothesized that women and men differ in their pursuit of careers in science, technology, engineering, and mathematics (STEM) owing to biological differences in mathematics aptitude. However, little evidence supports such claims. Some studies of children and adults show gender differences in mathematics performance but in those studies it is impossible to disentangle intrinsic, biological differences from sociocultural influences. To investigate the early biology of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
(55 reference statements)
1
18
0
2
Order By: Relevance
“…To summarize research on VSWM and spatial reasoning, Figure 1 was created to illustrate the involvement of the DLPFC, VLPFC, and the IPS areas. Areas illustrated in Figure 1 were similarly identified in a recent study of children aged 4-10, which suggests a lack of gender differences during mathematics development (Kersey, Csumitta, & Cantlon, 2019).…”
Section: Neuroimaging Correlatessupporting
confidence: 66%
“…To summarize research on VSWM and spatial reasoning, Figure 1 was created to illustrate the involvement of the DLPFC, VLPFC, and the IPS areas. Areas illustrated in Figure 1 were similarly identified in a recent study of children aged 4-10, which suggests a lack of gender differences during mathematics development (Kersey, Csumitta, & Cantlon, 2019).…”
Section: Neuroimaging Correlatessupporting
confidence: 66%
“…More controversial is the debate about the underlying causes. Arguments based on early biological differences in mathematical ability among the sexes do not seem to be supported by current experimental evidence (Hutchison, Lyons, & Ansari, 2018;Kersey, Csumitta, & Cantlon, 2019); actually, sociocultural influences rather than biological factors appear more likely to have an impact (Andreescu, Gallian, et al, 2008;Wang & Degol, 2016). Regardless, gender segregation concerning career preferences already manifests by high school and continues through college major choices.…”
Section: Related Workmentioning
confidence: 91%
“…Thus, on the basis of a review of studies of sex differences in human brain structure, Eliot concluded that when brain size is controlled for, sex category accounts for less than 2% of the variability in brain structure ( 19 ). Recent studies, which assessed the contribution of several factors to variability in brain function (measured using functional MRI), reported that sex category explained only a small fraction of this variability ( 20, 21 ). Finally, an assessment of the relations between the number of sex differences in functional MRI studies and sample size did not reveal the positive correlation expected if brain function of women and men belonged to two populations ( 22 ).…”
Section: Discussionmentioning
confidence: 99%